Irreversible cyclic cohesive zone model for prediction of mode I fatigue crack growth in CFRP-strengthened steel plates. (December 2020) - Mohajer, M.; Bocciarelli, M.; Colombi, P.; Hosseini, A.; Nussbaumer, A.; Ghafoori, E.
Highlights: The cyclic CZM describes the nonlinear processes associated to fatigue crack growth. The initiation, growth and retardation of crack are the natural outcomes of the model. Damage extrapolation via CZM parameters leads to high cycle fatigue simulation. The proposed FE model can be readily endowed with an interface TSL to predict the size and shape of the debonded region. Abstract: Experimental studies on various strengthening systems for steel elements under fatigue loading showed that the use of carbon fiber reinforced polymer (CFRP) strengthening system could significantly enhance the fatigue lifetime. Besides, more recently it was shown that the use of prestressed unbonded CFRP strengthening system results in an additional reduction of the fatigue crack propagation rate and promotes crack arrest. Different models have been proposed to evaluate the fatigue lifetime of CFRP-strengthened steel members (e.g. S-N curves and fracture mechanics-based models making use of Paris' law or similar). As an alternative approach in this study, the numerical assessment of mode I (tensile mode) fatigue crack growth of an existing macrocrack in unstrengthened and CFRP-strengthened (both nonprestressed bonded and prestressed unbonded) tensile steel members is investigated by using a cyclic cohesive zone model (CZM). The key advantage, compared to the above-mentioned methods, is that it introduces a constitutive relationship of the material, capable of being calibrated for different materials and being used for any geometry and loading condition. In this way, the crack initiation, crack propagation, crack retardation as well as crack arrest are the natural outcomes of the model. It is shown that the finite element (FE) model can be readily coupled with an interface traction-separation law (TSL), to predict the damage evolution in the steel-CFRP interface. The comparison between the numerical and experimental results validated the proposed FE modelling, which has also been used to perform a parametric study with respect to the main design parameters.